Pendampingan Remaja Desa dalam Mengatasi Permasalahan Pernikahan Dini melalui Komunitas PIK Remaja di Desa Wonokampir, Kecamatan Watumalang, Kabupaten Wonosobo - Ambar Teguh Sulistiyani; Aulia Putri Hijriyah; Nurmalita Shofia Hamiidah; Nanda Cindy Hendaliani; Miladiyatu Tsania Zulfa (Direktorat Pengabdian kepada Masyarakat, 2023)
One of the contributing factors of high population growth in Desa Wonokampir, Kecamatan Watumalang, Kabupaten Wonosobo, Central Java is the high number of early marriage cases, which has an impact on the high birth rate. This study aims to establish a Youth Information and Counseling Center (PIK) based mentoring system for early marriage cases in the local area. The research is an applied research based on action research by providing educational information. Data were collected through participant observation with the local community. The results showed that some of the causes of the high cases of early marriage were family economic factors and education. Early marriage can have an impact on health, one of which causes stunting. This statement was also supported by the explanation from the Wonokampir village midwife. Stunting occurs due to the condition of the fetus which has not grown properly due to the early gestational age. In an effort to reduce the number of early marriages in Desa Wonokampir, the KKN-PPM UGM team took the initiative to establish a PIK-Remaja program in Desa Wonokampir. This PIK-Remaja program has collaborated with PLKB Kecamatan Watumalang and Midwife in Desa Wonokampir. They assist in providing materials and mentoring to the youth in Desa Wonokampir. The applied research of this PIK-Remaja program provides an understanding of adolescents through information and counseling services on early marriage, reproductive health and family planning for adolescents so that they will have a better understanding of the importance of early marriage and family planning. In order to support Regulation of the Head of BKKBN Number 88/PER/F2/2012 about Guidelines for the Management of Information and Counseling Centers for Adolescents and the goals of Sustainable Development Goals (SDGs) points.